Nilai Pendidikan Karakter Tokoh Sri Ningsih dalam Novel “Tentang Kamu” Karya Tere Liye - Alya Hafizha (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research was conducted to increase the value of character education in children through written literary works, especially the novel entitled "The Value of Character Education for the Character Sri Ningsih in the Novel "Tentang Kamu" by Tere Liye". The problem underlying this research is the lack of character development in children, whether caused by parents or the environment. Therefore, the value of character education is very important for children, and it is important to instill the value of character education in literary works, because whether we realize it or not, literary works not only provide entertainment, but also have positive values ​​that can be applied. . In real life. One way to increase the value of character education in children is to encourage them to read books that attract attention and inspire. In this research, the researcher suggested reading the novel "About You" by Tere Liye by examining the character values ​​of the character Sri Ningsih. This research uses a qualitative descriptive method. So it is very important for us to research this research because it must ensure that children have strong personalities and good morals so that they can face life's challenges well and remember how great social and cultural diversity is in Indonesia.